(untitled) (Fiep Bulletin - online, 2013)
Objective: to describe the pregnant women attended at a Family Health Basic Unit (FHBU) knowledge about the importance of the diet in this period of their lives. Method: It was achieved a descriptive research with quantitative approaching. After inclusion and exclusion criterions, the sample was constituted of 32 pregnant women. The data collect was done through a structured interview form with close questions. It were obeyed the ethical principles of the 196/96 resolution of the Health National Council. It should be noted that this study was approved by the Ethics in Research of Santa Maria College, as Nº 517042010. Results: the majority of the interviewed ones were young, alphabetized, with remunerated work and married. The pregnant women received orientation about healthy food during pregnancy. The main foods said as important in pregnancy were: fruits, bean, meat, vegetables and milk. According to the diagnosed problems it was pointed out malnutrition and anemia. The food frequency was considered good, with an average of more than four daily meals. It was still pointed out that, to get an adequate diet is necessary to eat more fruits, vegetables and iron rich foods. Conclusion: The study made possible to describe pregnant women information regarding to the pregnancy period food importance. In front of these data, up to a point, the pregnant women were being oriented about the importance of a correct diet so they identify the relevant and indispensable foods in this period, even though, still present problems regarding to a bad diet.